Implementasi Perkembangan Artificial Intelligence Dalam Mengantisipasi Cyber Bullying Di Sd Negeri 1 Biting - Yusuf Bintang Tri Sakti; Siti Ayu Rina Nuryanti; Khoiril Bariyyah; Siti Sulistyowati; Adi Kusmanto (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
The rapid development of digital technology has created new educational opportunities while simultaneously increasing the risk of cyberbullying among elementary school students. Despite growing concerns regarding online harassment, limited attention has been given to integrating Islamic digital ethics and artificial intelligence (AI) literacy as preventive educational approaches in elementary education. This study aimed to introduce the concepts of cyberbullying prevention, Islamic digital ethics, and basic AI literacy to elementary school students through an educational outreach program. The activity was conducted as a community service initiative implemented by university students at an elementary school in February 2026. Data were collected through observations, interviews with school stakeholders, and documentation of student participation during the program. The findings indicate that students demonstrated a better understanding of cyberbullying, including its forms, consequences, and prevention strategies. Participants also showed increased awareness of responsible digital behavior, respectful online communication, and ethical social media use based on Islamic values such as respect, empathy, and avoiding harmful speech. Furthermore, students gained introductory knowledge of AI and its potential role in supporting safer digital environments. The novelty of this study lies in integrating Islamic digital ethics with AI literacy as an educational approach to strengthen cyberbullying awareness among young learners. These findings suggest that combining character education, digital ethics, and AI literacy can contribute to fostering responsible digital citizenship and creating safer online interactions in elementary education.